A cobertura jornalística da violência sexual contra crianças e adolescentes no jornal a crítica - Rodrigues, Geíne Medrado (Universidade Federal do Tocantins, 2021)
Child and adolescent sexual violence is a social problem of great proportions in Brazil. With the Covid-19 pandemic, there was an increase in the number of cases due to the crime occurring mainly in the family environment. Given this reality, journalism has a social responsibility to act in the discussion about sexual abuse and exploitation against children and adolescents based on the defense of their rights, thus contributing to the construction of citizenship for boys and girls. In this sense, this research aims to analyze news and reports that dealt with the theme of sexual violence against children and adolescents from July to December 2020. For this, we used as a methodology documentary research, in addition to content analysis applied in journalistic texts about the theme in the newspaper A Crítica. The results showed that in the coverage of the theme, the episodic framing and accountability approach predominates. Thus, it appears that the journalistic coverage of the topic still lacks quality from the production of news from the perspective of the rights of children and adolescents.